Life-Cycle Portfolio Choice with Additive Habit Formation Preferences and Uninsurable Labor Income Risk - Polkovnichenko, Valery (Review of Financial Studies, 2007)
This article explores the implications of additive and endogenous habit formation preferences in the context of a life-cycle model of an investor who has stochastic uninsurable labor income. To solve the model, I analytically derive the habit-wealth feasibility constraints and show that they depend on the worst possible path of future labor income and on the habit strength, but not on the probability of the worst income. When there is only a slim chance of a severe income shock, the model implies much more conservative portfolios. The model also predicts that for some low to moderately wealthy households, the portfolio share allocated to stocks increases with wealth. Because of this feature, the model can generate more conservative portfolios for younger than for middle-aged households. The effects of habits on portfolio choice are robust to income smoothing through borrowing or flexible labor supply. One controversial finding is that for high values of the habit strength parameter, usually required for the resolution of asset pricing puzzles in general equilibrium, the life-cycle model predicts counterfactually high wealth accumulation. (JEL: G11, G12) Copyright 2007, Oxford University Press.